Ecophysiological and nutritional characterisation of two morphotypes of Cakile maritima subsp. maritima Scop. from Puglia region, Southern Italy - Conversa, Giulia; Botticella, Lucia; Lazzizera, Corrado; Bonasia, Anna; Elia, Antonio (Frontiers in Plant Science, 2024)
Cakile maritima subsp. maritima Scop. (sea rocket) is a succulent halophyte with significant potential as a nutritious food source, being rich in essential nutrients such as vitamins, minerals, and antioxidants. This annual species exhibits two distinct leaf morphotypes: entire lamina (EL) and pinnatifid lamina (PL). Our understanding of their ecophysiological and nutritional profiles is still limited. The present study investigated the wild EL and PL sea rocket plants from southern Italy during their vegetative stage. The bio-morphological traits (leaf mass area-LMA, dry matter and chlorophyll concentrations), main inorganic ions, key antioxidants (carotenoids, anthocyanins, phenols, flavonoids, glucosinolates, vitamin C as ascorbic and dehydroascorbic acid), and antioxidant activity (by FRAP, DPPH, ABTS assays) were analyzed. Additionally, photosynthetic gas exchange and chlorophyll fluorescence were measured. PL plants showed thicker leaves (higher LMA) and greater accumulation of photo-protective pigments (carotenoids and anthocyanins), despite similar chlorophyll levels. The PL plants also demonstrated higher photosynthetic activity, transpiration rates, and stomatal conductance, with reduced non-photochemical quenching. The EL morphotype had higher cation (K, Mg, Ca, Na) and vitamin C (135.3 mg 100 g-1 FW) concentrations, while no significant disparities were observed between the morphotypes in phenolic concentration (208.5 mg g.a.e. 100 g-1 FW), flavonoids (71.5 mg q.e. 100 g-1 FW), or glucosinolates (61 mg g-1 FW). Interestingly, while the EL type had higher vitamin C, the PL morphotype showed superior antioxidant activity (FRAP, DPPH) and seems to be better adapted to water/nutrient scarcity typical of southern Italy. Both morphotypes offer potential as high-nutritional foods, however, future research should investigate the genotype-specific production of antioxidant compounds in EL and PL plants in response to environmental stresses, including salinity for potential exploitation as a new crop.